Correlates of psychological well-being amongst graduate students in Malaysia - Panahi, Soheila; Md. Yunus, Aida Suraya; Roslan, Samsilah (Marsland Press, 2013)
The aim of this study was to examine whether there are differences in psychological well-being among graduate students in terms of demographic profile namely faculty, age, race, number of semesters of study, gender, marital and employment status and family size. Psychological well-being is measured using the Scales of Psychological Well-being with six dimensions including: autonomy, environmental mastery, personal growth, positive relationships with others, purpose and self-acceptance. A total of 534 graduate students (155 males and 379 females) were randomly selected in one Malaysian university. Data was analyzed using one-way ANOVA, and independent t-test. The finding of this study revealed significant differences in overall psychological well-being in terms of different faculties, ages, semesters of study, genders, marital status. As for differences in overall psychological well-being, it was established that there is significant differences in personal growth and positive relationship between students of different semesters of study. In addition, the result indicated that there is significant positive relationship among different semesters of study, ages, genders, and marital status. Significant difference in purpose in life was found for students of different gender and marital status. Moreover, this study showed that marital and employment status have a significant difference in autonomy while, the marital status showed positive and significant difference for overall psychological well-being, positive relationship, purpose in life, and self-acceptance. However, there are no significant differences in psychological well-being of graduate students across different races and family sizes.